CFD Analysis of Heat Exchanger Effectiveness and LMTD with Varying Pipe Length - Al-Rawashdeh, Shahed A. (Ital Publication, 2025)
This paper presents a new numerical analysis for 2D heat exchanger (HE) model by employing computational fluid dynamics (CFD) simulations to analyze the impact of pipe length on the efficiency and the Log Mean Temperature Difference (LMTD) of parallel and counterflow double-pipe heat exchangers while maintaining constant flow rates, inlet temperatures, and fluid properties. The findings demonstrate that heat exchanger efficiency and LMTD in both the parallel and counter-flow HEs are significantly influenced by pipe length, with longer heat exchangers improving heat transfer effectiveness by allowing more time for thermal exchange, larger heat exchange surface area, and achieving a more uniform temperature distribution. Counterflow heat exchangers also showed higher efficiencies at all lengths than parallel flow heat exchangers due to the larger temperature difference between the fluids. These insights are particularly valuable for engineers and designers seeking to optimize heat exchanger configurations for industrial applications, where enhancing heat transfer efficiency and minimizing energy losses are critical for cost-effective and sustainable thermal management systems.